On the issue of military-patriotic education of primary school children with disabilities - Argandeikina E. S. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article presents the issue of the organization of work on military-patriotic education of primary school children with disabilities. It is noted that in the conditions of multinational Russia in the school education system, the problems of fostering not only respect for other nations, but also love for the motherland become important. Patriotism implies pride in the achievements and culture of one's homeland, the desire to preserve its characteristics, as well as identification with other representatives of one's nation, a willingness to give preference to the interests of one's country and a desire to protect the interests of the motherland and the people.
Keywords: ограниченные возможности здоровья; младший школьный возраст; limited health opportunities; военно-патриотическое воспитание; primary school age; military-patriotic education